Flood Inundation Mapping of Chiang Khwan District, Roi Et by Coupled 1D/2D Hydraulic Model - Prabnakorn, Saowanit; Sirapojanakul, Supkakorn; Lipiloet, Sukhom (Frontiers in Engineering Innovation Research, 2022)
Chiang Khwan district in Roi Et has been experienced recurring floods. Over the past 12 years (2010-2021), 9 flood events occurred at Chiang Khwan, resulting in the loss of lives and properties. This research aims to identify flood areas at Chiang Khwan district at 2-, 5-, 10-, 25-, 50- and 100-year return periods. The design floods and water level elevations are estimated by the Gumbel distribution. Those are inputs into a 1D/2D hydraulic model of the Chi River developed for flood inundation mapping. At satisfactory calibration and validation results, the R2 > 90% and RMSE < 1 m, the model demonstrates that, at the above return periods, approximately 22,792; 36,554; 39,053; 41,476; 43,965 และ 45,349 rai are inundated, respectively. For the 2- and 5-year return periods, the flood depths vary mostly between 0-2 m, and that for other return periods vary mostly between 0-4 m. The flooding begins at Chiang Khwan sub-district, located shortly downstream of the Lam Pao, which receives water from Lam Pao Dam. However, after a while, due to narrower river cross-sections downstream, which significantly reduce the river’s drainage capacity, a huge volume of water accumulates, overflows its banks, and starts flooding downstream. As a result, Phlapphla, Phra That, and Chiang Khwan sub-districts are most affected, respectively. This information and flood inundation maps are useful for developing flood-control measures, flood resilient design, and emergency action plan to protect and reduce adverse impacts from future floods.